2016
DOI: 10.21082/ijas.v10n1.2009.19-25
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Seedling Root Growth Promotion by 1-Aminocyclopropane-1-Carboxylate Deaminase-Producing Pseudomonads

Abstract: Pseudomonad producing 1-aminocyclopropane-1-carboxylate (ACC) deaminase (E.C.4.1.99.4) has been known to promote plant growth by lowering ethylene biosynthesis in higher plants, which can be induced by indole-3-acetic acid (IAA) production. The objective of this study was to examine the ability of IAAproducing Pseudomonas isolated from local soil environment (rhizosphere of soybean grown in Plumbon's agricultural area<br />in Cirebon, West Java, Indonesia) to promote soybean root growth in relation to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Similarly, the screening of 563 bacteria isolated from the roots of pea, lentil and chickpea showed that only 5% isolates showed ACC deaminase activity and 7% isolates were capable of indole acetic acid production (Hynes et al, 2008). Husen et al (2009) observed that 11 out of total 13 Pseudomonas isolates possessed ACC deaminase activity and increased root development of soybean. Khandelwal and Sindhu (2012) found that 38.9% Pseudomonas isolates obtained from clusterbean rhizosphere showed good growth on ACC supplemented plates.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the screening of 563 bacteria isolated from the roots of pea, lentil and chickpea showed that only 5% isolates showed ACC deaminase activity and 7% isolates were capable of indole acetic acid production (Hynes et al, 2008). Husen et al (2009) observed that 11 out of total 13 Pseudomonas isolates possessed ACC deaminase activity and increased root development of soybean. Khandelwal and Sindhu (2012) found that 38.9% Pseudomonas isolates obtained from clusterbean rhizosphere showed good growth on ACC supplemented plates.…”
Section: Discussionmentioning
confidence: 98%
“…High density inoculum (10 8 CFU.mL −1 ) exhibited negative effect on plant root development whether grown in soil or on MS Agar. A number of reasons could account for this, for example: (i) higher inoculation might lead to more IAA production, which would induce ethylene production and thus inhibit root growth and development (Husen et al 2009 ); (ii) high density inocula could produce plant growth harmful metabolites inhibiting root development as shown in Convolvulus arvensis L (Sarwar and Kremer 1995 ); or (iii) high microbial titres may elicit plant defence mechanisms such as microbial associated molecular patterns (MAMPS) with adverse plant growth effects (Doornbos et al 2012 ). However, because the high density Klebsiella SGM 81 inoculum resulted in poorer health of D. caryophyllus that correlated with a rapid decline in the rhizospheric bacterial population but not in a decline of endophytic bacteria, we propose that whatever the cause of poor plant health, the decline of rhizophere bacterial population is mainly attributable to a lack of positive effects of the plant towards bacteria, rather than a plant defence mechanism that would also target endophytic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative detection of 1‐aminocyclopropane‐1‐carboxylate (ACC) deaminase produced by the isolates was performed using DF‐ACC salts minimal medium (Husen et al . ). After 24 h, cells were collected, watered, and dilapidated.…”
Section: Methodsmentioning
confidence: 97%